Correction: Impact of visual impairment on balance and visual processing functions in students with special educational needs. - Kai Yip Choi; Ho Yin Wong; Hoi Nga Cheung; Jung Kai Tseng; Ching Chung Chen; Chieh Lin Wu; Helen Eng; George C Woo; Allen Ming Yan Cheong (PLoS ONE, 2023)
[This corrects the article DOI: 10.1371/journal.pone.0249052.].